(untitled) (Architecture Image Studies, 2025)
In developing countries, tourism industries offers promising economic development with a positive outcome. However, the tourism industry is subjected to the certain limitation in terms of the inhabitants of the local and ecological community. It provides the hardship for the tourism in native people in emphasize of culture and environment as an important factor in ecotourism. The evolution of ecotourism engaged in the provision of environmental pollution-free. The concept of ecotourism is still an emerging concept in the provision of results and overall prospects of the environment. For this, it is necessary to evaluate the ecotourism potential and perception to evaluate the relationship between environmental conservation and ecotourism. This research aimed to evaluate ecotourism in India in terms of natural and cultural terms for evaluation of the relationship between ecotourism and conservation. The examination of ecotourism is based on an evaluation of the relationship between tourists’ perception and conservation agencies in India. The analysis of results revealed that there exists a positive relationship between ecotourism and environmental conservation in terms of conservation agencies and tourists perception. Also, it is identified that there is no significant difference lies between conservation agencies’ and tourists perception with the evaluation of the positive relationship between environmental conservation and ecotourism in India. Through analysis, the to improve energy conservation and ecotourism in India are suggested.